Anaemia and Iron Homeostasis in a Cohort of HIV-Infected Patients: A Cross-Sectional Study in Ghana - Christian Obirikorang; Razak Gyesi Issahaku; Derick Nii Mensah Osakunor; James Osei-Yeboah (AIDS Research and Treatment)
Aim. We determined the prevalence of anaemia and evaluated markers of iron homeostasis in a cohort of HIV patients. Methods. A comparative cross-sectional study on 319 participants was carried out at the Tamale Teaching Hospital from July 2013 to December 2013, 219 patients on HAART (designated On-HAART) and 100 HAART-naive patients. Data gathered include sociodemography, clinical history, and selected laboratory assays. Results. Prevalence of anaemia was 23.8%. On-HAART participants had higher CD4/CD3 lymphocyte counts, Hb, HCT/PCV, MCV, MCH, iron, ferritin, and TSAT (P<0.05). Hb, iron, ferritin, and TSAT decreased from grade 1 to grade 3 anaemia and CD4/CD3 lymphocyte count was lowest in grade 3 anaemia (P<0.05). Iron (P=0.0072) decreased with disease severity whilst transferrin (P=0.0143) and TIBC (P=0.0143) increased with disease severity. Seventy-six (23.8%) participants fulfilled the criteria for anaemia, 86 (26.9%) for iron deficiency, 41 (12.8%) for iron deficiency anaemia, and 17 (5.3%) for iron overload. The frequency of anaemia was higher amongst participants not on HAART (OR 2.6 for grade 1 anaemia; OR 3.0 for grade 3 anaemia). Conclusion. In this study population, HIV-associated anaemia is common and is related to HAART status and disease progression. HIV itself is the most important cause of anaemia and treatment of HIV should be a priority compared to iron supplementation.